(untitled) (Global Journal of Human-Social Science, 2014)
Gender biases exist in form of laws and customs that continue to impede female access to make imputes into developmental process. Economic and domestic workloads also impose severe time burden on the feminine gender. Educationally, feminine gender have mostly affected by these negative factors as the National literacy rate for female is lower compared to that of males. In certain states of the federation, the female literacy enrolment and achievement rates are much lower. This is against the fact that education is a basic and fundamental right of all citizens. This study examines whether or not gender roles assigned to feminine gender affect their school performance; the extent gender is used to discriminate feminine gender for access to school. Findings from this study include: Assisting in rearing the going ones is time consuming and it affects educationally performance of girl child or no payment of school fees and sexual harassment. For gender social equality to be achieved and sustained, there is the need for female education to fill the gap. Negative cultures should be adjusted; teachers should stop devaluing girls by and gender equality should be adhered to in any society.ridiculing them and enhancement of women education.